Peixes como modelo biológico para o monitoramento ambiental em áreas agrícolas - Severo, Eduardo Stringini (2021)
The high demand for food has led to a greater number of pesticides used in crops, causing an environmental impact on aquatic environments near these locations. To assess the impacts on aquatic environments, biomonitoring studies are needed. Fish are commonly used as an animal model to carry out this type of study. The state of Rio Grande do Sul is among the largest agricultural producers in Brazil, but the region lacks studies on the presence of contaminants in its rivers and streams. In Article 1, the objective was to carry out a review of the main biomonitoring methodologies carried out in Latin American countries. Thus, 127 scientific articles published between 2010 and 2020 reporting the implementation of biomonitoring methodologies in aquatic environments using fish as bioindicators of environmental pollution were analyzed. Thus, the main advantages and disadvantages of each methodology were evaluated, as well as the main analyzes carried out during and after the biomonitoring studies. In article 2, Danio rerio embryos were used as bioindicators to assess water quality in the Vacacaí River. They carried out 8 water collections at three points in the river during the year 2018. The collected waters were used to quantify pesticides and expose the embryos for 96 hours. Twenty-four pesticides were found in river water samples. The most common were atrazine, quinclorac and clomazone. During the exposure, spontaneous movement, heart rate and hatching rate were evaluated. After the end of exposure, the embryos were euthanized for biochemical assays. Biomarkers such as thiobarbituric acid reactive substance (TBARS), acetylcholinesterase (AChE), glutathione S-transferase (GST) and catalase (CAT) were analyzed. Increases in GST and TBARS were observed, especially during periods of greater water contamination, such as January, February, October and November. In Article 3, zebrafish embryos were exposed to the herbicide Basagran® at the concentrations of its active principle (bentazone) found in the biomonitoring study carried out in Article 2. The aim of the study was to evaluate the development of embryos of D. rerio exposed to environmental concentrations of this herbicide (3 μg.L-1, 6 μg.L-1, 12 μg.L-1), as well as its established safe limit for drinking water (300 μg.L-1) . Behavioral and developmental analyzes were performed during the exposure period. The results showed alterations only in the heart rate evaluated in 48 hours after fertilization, showing that the herbicide Basagran® at the tested concentrations caused few adverse effects on the development and behavior of the evaluated embryos. In general, the possibility of using zebrafish embryos to carry out biomonitoring studies was found.